Das slavische Lehngut im Albanischen Teil 2: Ortsnamen - Ylli, Xhelal (Slavistische Beitraege, 2000)
The present work represents the second part of the study on Slavic fiefdom in Albanian (SB 350) and deals with the Slavic place names of Albania. In the center of this part are the Slavic place names: names of cities, area names and villages names of Albania, which are considered under different aspects. First, the inventory and geographic distribution for each district of Albania are determined, and then the formation types, the onymic contents, and the oldest place names are represented in their respective geographical distribution. On the basis of this work, the already published volume on the loanwords and the planned volume on the waters and field names of Albania, a reconstruction of the historical relations between Albanians and southern slaves is to be facilitated.